2020
DOI: 10.1055/a-1263-0747
|View full text |Cite
|
Sign up to set email alerts
|

Poor Perception of School Toilets and Increase of Functional Constipation

Abstract: Objective A suggested mechanism of functional constipation (FC) is the refusal against painful bowel movements and a vicious circle of holding back stool, hardening, colonic dilatation and further painful defecation. The aim of this study is to describe perception of school toilets, prevalence of functional abdominal pain (FAP) and constipation in elementary schools. Design and Setting All elementary schools in Giessen County, Germany were contacted. Parents received a questionnaire on perception of toilets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…Lower school children from Sweden gave a median of “3” in the evaluation of school toilets (1, terrible; 5, excellent) [ 46 ]. A parent survey conducted in Giessen (Germany) asked whether their children used the sanitary facilities at school [ 47 ]. Similar to our study, children´s avoidance behavior was evident in relation to toileting at school.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower school children from Sweden gave a median of “3” in the evaluation of school toilets (1, terrible; 5, excellent) [ 46 ]. A parent survey conducted in Giessen (Germany) asked whether their children used the sanitary facilities at school [ 47 ]. Similar to our study, children´s avoidance behavior was evident in relation to toileting at school.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our study, children´s avoidance behavior was evident in relation to toileting at school. In addition, over 75.0% of parents indicated that children predominantly use the sanitary facilities to urinate only, but less for bowel movements [ 47 ]. Swedish school children also stated that the sanitary facilities at school were more likely used for urinating [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“… 16 Children may also be deterred from using public toilets because of a lack of privacy or, more commonly, the absence of toilet paper and poor sanitary conditions. 17 , 18 Travelling disrupts the normal toilet routine and toilet facilities may not be easily accessible. A disturbed parent–child relationship and emotional stress may also result in irregular bowel habits in children.…”
Section: Aetiopathophysiologymentioning
confidence: 99%
“…Environmental, behavioural, immunological and genetic factors may contribute to functional constipation [ 9 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The typical mechanism is behavioural stool withholding because of pain, inflammation or anal fissure, which can lead to a vicious cycle of large, firm, painful stools and further withholding [ 12 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental, behavioural, immunological and genetic factors may contribute to functional constipation [ 9 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The typical mechanism is behavioural stool withholding because of pain, inflammation or anal fissure, which can lead to a vicious cycle of large, firm, painful stools and further withholding [ 12 , 18 , 19 , 20 , 21 , 22 ]. Children with autism, neurological or motor disorders, developmental, psychiatric and behavioural conditions, atopy and food allergies and children exposed to abuse, violence or psychological stress are more prone to develop constipation [ 18 , 19 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ,…”
Section: Introductionmentioning
confidence: 99%